Neopterin as a marker for immune system activation in coal workers' pneumoconiosis - Ulker, Ozge C.; Yucesoy, Berran; Durucu, Murat; Karakaya, Asuman (Toxicology and industrial health, 2007)
Coal workers' pneumoconiosis (CWP) is an occupational pulmonary disease that occurs by chronic inhalation of coal dust. Coal workers' pneumoconiosis is divided into two categories depending on the extent of the disease as simple pneumoconiosis (SP) and progressive massive fibrosis (PMF). Development of CWP is associated with the activation of the immune system. Neopterin is a predictive biochemical marker of cell-mediated immune activation and elevated levels of neopterin are detected in body fluids of patients with immune-related diseases. The present study was aimed to investigate whether increased serum, urine and bronchoalveolar lavage (BAL) fluid levels of neopterin is associated with the development and/or severity of CWP. Mean serum neopterin levels in SP and PMF patients (10.72 ± 0.98 nmol/L; 14.08 ± 3.86 nmol/L, respectively) were significantly higher than those of control group (5.30 ± 0.47nmol/L) (P < 0.05). Although urinary neopterin levels were also increased in SP and PMF patients (235.17 ± 7.40 μmol/mol creatinine; 256.05 ± 9.43 μmol/mol creatinine, respectively) as compared with the control group (140.00 ± 5.43 μmol/mol creatinine) (P < 0.01), they were within the normal concentration range. No significant difference was observed between serum and urinary neopterin levels of SP and PMF patients. A correlation was observed between serum and urinary neopterin levels of all subjects (r = 0.525, P < 0.01). Bronchoalveolar lavage fluid neopterin levels were significantly higher in patients with SP and PMF (22.67 ± 2.9 nmol/L; 41.67 ± 8.68nmol/L, respectively) compared with control subjects (6.264 ± 1.74 nmol/L) (P < 0.05, P < 0.01, respectively). The levels of neopterin in BAL fluid were also significantly higher in patients with PMF than in those with SP ( P < 0.05). These findings indicate that elevated serum and BAL levels of neopterin may be considered as a suitable biomarker for the assessment of CWP. Toxicology and Industrial Health 2007; 23: 155—160.